Burnout and its relationship with Stress among Nurses during Corona pandemic - Field study in Mohamed Boudiaf Hospital-Médéa - Haireche, Redha; Belhaouari toufik, Brahim (Milev Journal of Research and Studies, 2022)
The current study aimed at identify the level of psychologicalBurnout and its relationship with the Stress among Nurses during the Corona pandemic) nCov19 (, Based on the descriptive approach and used two tests, Maslash Burnout Scale and Beck stress test, The study sample consisted of (140) nurses from Mohamed Boudiaf Hospital in Médéa , different ages and sex, As well as identifying the differences in each dimension of psychological burnout, and stress. The study concluded that nurses suffer from varying levels of psychological burnout, also did not reveal any significant differences in the level of psychological burnout by sex variant.